3-4(x+3)=6x-29

Simple and best practice solution for 3-4(x+3)=6x-29 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3-4(x+3)=6x-29 equation:


Simplifying
3 + -4(x + 3) = 6x + -29

Reorder the terms:
3 + -4(3 + x) = 6x + -29
3 + (3 * -4 + x * -4) = 6x + -29
3 + (-12 + -4x) = 6x + -29

Combine like terms: 3 + -12 = -9
-9 + -4x = 6x + -29

Reorder the terms:
-9 + -4x = -29 + 6x

Solving
-9 + -4x = -29 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-9 + -4x + -6x = -29 + 6x + -6x

Combine like terms: -4x + -6x = -10x
-9 + -10x = -29 + 6x + -6x

Combine like terms: 6x + -6x = 0
-9 + -10x = -29 + 0
-9 + -10x = -29

Add '9' to each side of the equation.
-9 + 9 + -10x = -29 + 9

Combine like terms: -9 + 9 = 0
0 + -10x = -29 + 9
-10x = -29 + 9

Combine like terms: -29 + 9 = -20
-10x = -20

Divide each side by '-10'.
x = 2

Simplifying
x = 2

See similar equations:

| 2(6y-1)=-38 | | 2.5x+3=0.5x-9 | | 2xy-3xy=0 | | 9-2x+6=5x+1 | | 1/3x=1/5 | | (2ab)^3/(2a^-2b^-2)^2 | | x+3y+z=2 | | 3[9-(-3x-6)]=81x+189 | | 2.65lb/o.5025qt= | | 19.6x=128 | | y/8-4=3 | | 2x+8=-3x-7 | | 81n^2-225=0 | | 1/33 | | 2x-3+-3=2x+6 | | 2(x-1)=-x+7 | | -80=2/3x-6x | | 3/7x5/7x1/2 | | .0132xy-0.4183x+0.1896y=0 | | -48/60 | | (5X-6)=3X+4 | | ln(x^2-x)=ln(30) | | 2x^3+11x^2+17x+6=0 | | 174=2(4y)+2(3y+3) | | 24x^2+99x+12= | | 4x-4y+7-1= | | -15x+31p=62 | | 174=2(4x)+2(5x-3) | | 6x-2/3x=80 | | 20t(t+3)=19t-20 | | x/.1=900 | | 80=4x+x+3+5x-3 |

Equations solver categories